Transcriptome profiles of rice roots under simulated microgravity conditions and following gravistimulation - Kuya, Noriyuki; Nishijima, Ryo; Kitomi, Yuka; Kawakatsu, Taiji; Uga, Yusaku (Frontiers in Plant Science, 2023)
Root system architecture affects the efficient uptake of water and nutrients in plants. The root growth angle, which is a critical component in determining root system architecture, is affected by root gravitropism; however, the mechanism of root gravitropism in rice remains largely unknown. In this study, we conducted a time-course transcriptome analysis of rice roots under conditions of simulated microgravity using a three-dimensional clinostat and following gravistimulation to detect candidate genes associated with the gravitropic response. We found that HEAT SHOCK PROTEIN (HSP) genes, which are involved in the regulation of auxin transport, were preferentially up-regulated during simulated microgravity conditions and rapidly down-regulated by gravistimulation. We also found that the transcription factor HEAT STRESS TRANSCRIPTION FACTOR A2s (HSFA2s) and HSFB2s, showed the similar expression patterns with the HSPs. A co-expression network analysis and an in silico motif search within the upstream regions of the co-expressed genes revealed possible transcriptional control of HSPs by HSFs. Because HSFA2s are transcriptional activators, whereas HSFB2s are transcriptional repressors, the results suggest that the gene regulatory networks governed by HSFs modulate the gravitropic response through transcriptional control of HSPs in rice roots.